Una nueva interpretación de "El cacique de Turmequé" de Gertrudis Gómez de Avellaneda - Pérez Bernardo, María Luisa (Verba hispanica, 2014)
Gertrudis Gómez de Avellaneda is remembered for her controversial and progressive beliefs. She established a reputation early in her career as a talented writer whose unconventional behavior was as well known as her works. During her lifetime, Avellaneda enjoyed literary and commercial success in several genres, including poetry, drama, essays, and lengends. In the legend "El cacique de Tumequé" written in 1860 and published in 1871, Gertrudis Gómez de Avellaneda re-interpretes Juan Rodríguez Freyle's El carnero o conquista y descubrimiento del Nuevo Reino de Granada (1636-1638). Through this essay it will be displayed how Avellaneda with "The cacique of Turmequé" presents a vision of Nueva Granada distinct to that of the chronicler Juan Rodríguez Freyle. In this way, the female writer manipulates historical time, to propose to the Spanish public of the 19th century another version of the conquest, one that was not that of the victors, but of the vanquished; distancing herself from the dominant discourse of her time. In "El cacique de Tumequé", Avellaneda challenges the political power of the colonial era that positioned women as inferior human beings. In her narrative, she breaks away from the established order, especially against the misogynist remarks from El carnero, a chronicle that consistently criticized and ridiculed women. Gómez de Avellaneda%s work deconstructs the social and political institutions that emphasized the idea that women were intellectually subordinate. Moreover, in "El cacique de Turmequé" she defendes the dignity of the indigenous population, by reaffirming their integrity and liberty in the colonial society.
Keywords: Gómez de Avellanada, Gertrudis, 1814-1873; latinskoameriška književnost; kubanska književnost; kronike; zgodovinski čas; legende